2009
DOI: 10.1577/h08-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Selected Immune‐Relevant Genes in Channel Catfish during Edwardsiella ictaluri Infection

Abstract: Channel catfish Ictalurus punctatus were intraperitoneally challenged with the bacterium Edwardsiella ictaluri (the causative agent of enteric septicemia of catfish), and the expression of genes presumed to function in the inducible innate defense was evaluated. End-binding protein 1 (EB1), beta1-integrin, natural-resistance-associated macrophage protein (Nramp), heat shock protein 70 (Hsp70), serum amyloid P (SAP), and transferrin gene expression profiles were determined using quantitative reverse-transcripta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 70 publications
3
12
0
Order By: Relevance
“…Otherwise, molecular methods have early indicated the increase of HSP70 transcripts in fish submitted to bacterial challenge (Elibol-Flemming et al, 2009;Dang et al, 2010). Similarly, the present study showed the up-regulation of the HSP70 in the thymus of L. anguillarum-infected fish.…”
Section: Discussionsupporting
confidence: 76%
“…Otherwise, molecular methods have early indicated the increase of HSP70 transcripts in fish submitted to bacterial challenge (Elibol-Flemming et al, 2009;Dang et al, 2010). Similarly, the present study showed the up-regulation of the HSP70 in the thymus of L. anguillarum-infected fish.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, spleen and head kidney hsp60 expression was consistently lower than that in liver tissue during heat stress. Elibol-Flemming et al (2009) demonstrated that splenic hsp70 expression is significantly lower than in the liver during acute-phase cell-stress responses. This suggests that the spleen and head kidney might have adapted to some chronic stressors, or that there may be other regulatory mechanisms involved.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the transcriptional levels of five toll-like receptors (TLRs) have been reported to be upregulated by acute infection with E. ictaluri [38]. Furthermore, the expression levels of tumor necrosis factor a (TNFa) [39], interleukin (IL)-1b [39], IL-10 [39], chemokine CXCL10 [40], hepcidin [32,41], bactericidal permeability-increasing protein [42], liver-expressed antimicrobial peptide-2 [43], transferrin [44], and cathepsin D [45] in channel catfish have been reported to be upregulated by bacterial infections. In addition, three channel catfish NK-lysine genes have been reported to be expressed in the anterior kidney of uninfected fish [46].…”
Section: Genes Reported In Literatures Screened In This Studymentioning
confidence: 99%